TEACHING LEARNING MEDIATED BY NETWORKING TECHNOLOGIES: COMPLEXITY OF FACULTY PERFORMANCE - Elena Maria Mallmann; Anna Helena Silveira Sonego; Juliana Sales Jacques; Iris Cristina Datsch Toebe; Fabiane da Rosa Domingues; Mara Denize Mazzardo (Editora da Universidade de Santa Cruz do Sul, 2013)
The main goal of this article is to analyze the faculty performance as a complex process in higher education mediated by the educational technology network. We elected the problem posing dialogue educational model from Paulo Freire and the Mediators Network theory of Bruno Latour as postulates of theoretical foundations. The methodological procedures are exploratory descriptive based on a questionnaire-like survey customized to action research mediated by technology network. The triangulation data analysis evince as a result that the faculty performance dispenses technological pedagogical fluency to the interactivity development and interaction in Teaching Learning in Virtual Environments. The conclusive emphasis indicates the necessity of investments in the continuous formation of professors to consolidate the integration of educational technology network and the convergence between modalities.